Effect of age on sensory perception of beef patties with varying firmness. (October 2022) - Mena, Behannis; Hutchings, Scott C.; Ha, Minh; Ashman (dec.), Hollis; Shand, Phyllis J.; Warner, Robyn D.
Abstract: Sensorial perceptions change as people age; hence the aim of this study was to test if there were differences between younger ( n = 95; aged 20-56) compared to older ( n = 97; aged 60-81) consumers in sensory assessment of beef patties with varying firmness ('soft', 'medium', 'hard') and the influence of adding plum sauce as a lubricant and flavouring. The firmness of patties influenced consumer scores for overall liking, appearance, texture, flavour, and saltiness for both age groups. Both groups preferred the 'soft' patty regardless of sauce addition. When sauce was added, there was an increase in appearance and texture liking for younger consumers, but it did not influence liking for older people. In contrast to older consumers, younger subjects noted a ' sour-acidic ' taste in samples. Sensorial perception of flavour does change as people age, and this is important to consider when developing suitable foods for older adults' consumption. Highlights: Hardness affects consumer liking of beef patties. Younger consumers better discriminated texture and flavour differences of beef patties. Consumption of beef patties with sauce increased liking of beef patties for younger consumers. Beef patties perception and acceptability depends on age of consumer.